OVARIAN FOLLICULAR DYNAMICS IN Gn-RH ANTAGONIST TREATED HEIFERS DURING THE PERIOVULATORY PERIOD - Bambang Poernomo S. (The East Java Biological Society, 1999)
It is not clear wheter the turnover of ovaries follicles during the periovulatory period in Gn-RH treated heifers. This study was performed to test the hypothesis that an increase dosage of Gn-RH antagonist influences the follicular development. Six normocyclic black pied heafers was derived into equally two control and treatment groups. The injection of Gn-RH antagonist Antarelix ® (Eurpeptides, France) and vehicle (mannitol) were performed six times every 12 hours on the day-1, 0, 1 and 2, respectively. Ultrasound examinations of the ovaries can carried out using B-mode scanner and performed every day beginning from day 0. Result of the study suggest all animals showed sign of behaviorial estrous begining around 52 hours after induction of luteolysis. All control animal showed the development of a large (more than eight mm diameter) preovulatory follicle with maximum diameters between 11 and 15 mm and thereafter ovulated. Two of there controls ovulated between days 1 and 2 the remining control heifer showed ovulation between days 2 and 3. Treated animals developed large follicles with maximum diameter between 12 and 17 mm but they did not ovulate. Concerning the number of small (one to less than four mm diameter) and medium (four to eight mm diameter) follicles there were no significantly differences found between control and treated animals. However, Antarelix ® did not inhibit the development of all follicles. Antarelix ® also did not inhibit the development fo large follicles but inhibited ovulations.